Characters and Non-Digital Media: Case Study Trends in English Language Learning in Secondary Schools - Mas'odi, Mas'odi; Arma, Icha Pebly (Assyfa Journal of Multidisciplinary Education, 2023)
This research highlights the role of characters and non-digital media in English language learning in secondary schools, focusing on case study trends over the last decade (2014-2024). This research aims to evaluate the effectiveness of the use of textbooks, printed materials, and direct interaction between teachers and students in the context of English learning. The methodology used is a systematic literature review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method, where the selected literature comes from Scopus-indexed journals. The literature selection process involved strict inclusion criteria, including research involving students and teachers from various backgrounds and regions. The research results show that non-digital media such as textbooks and physical teaching aids still have an important role in learning, with a significant contribution in increasing student engagement and understanding. In addition, the characteristics of a dedicated teacher and a personal approach have been proven to have a strong correlation with learning success. However, the research also revealed shortcomings in the existing literature, such as a lack of focus on holistic integration between digital and non-digital media. This includes the absence of a balanced learning strategy that utilizes the advantages of both types of media. This research recommends the development of balanced and holistic learning strategies that can maximize student learning outcomes through the optimal use of both types of media. In addition, further research is needed to explore ways of more effective integration between digital and non-digital media in English language learning contexts. These findings can be a basis for developing more innovative and effective curricula and teaching methods in the future.